2015
DOI: 10.1039/c4cc08977d
|View full text |Cite
|
Sign up to set email alerts
|

Direct fabrication of nanoporous graphene from graphene oxide by adding a gasification agent to a magnesiothermic reaction

Abstract: CaCO3 acts as a gasification agent during magnesiothermic reduction of graphene oxide, thus preventing the newly formed graphene from restacking. The surface area of the obtained graphene increases from 66 m(2) g(-1) to 603 m(2) g(-1) by adding CaCO3 with a high yield of ∼70% based on the carbon content in graphene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Hence, it can be concluded that the rGO present in the composite is not contributing significantly to the capacity; rather it improves the interfacial electron transfer in between MoS 2 and rGO surfaces during charge/discharge process. Further rGO induces an increased porosity and high surface area of the composite material 37 38 which can facilitate transport of solvated Na-ion through the electrode, as a result of which, Na + can reach each part of electrode materials. rGO can also act as a mechanical buffer to ensure that no change in the electronic connectivity of MoS 2 nanoflowers occurs due to the volume change encountered during sodiation/desodiation and helps to maintain the structural integrity of the composite electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it can be concluded that the rGO present in the composite is not contributing significantly to the capacity; rather it improves the interfacial electron transfer in between MoS 2 and rGO surfaces during charge/discharge process. Further rGO induces an increased porosity and high surface area of the composite material 37 38 which can facilitate transport of solvated Na-ion through the electrode, as a result of which, Na + can reach each part of electrode materials. rGO can also act as a mechanical buffer to ensure that no change in the electronic connectivity of MoS 2 nanoflowers occurs due to the volume change encountered during sodiation/desodiation and helps to maintain the structural integrity of the composite electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The difference of domain sizes may relate to melting points of metals, which are 2623, 3422, 1246, 1495, 419, and 1668 °C for Mo, W, Mn, Co, Zn, and Ti, respectively. Based on our previous studies, LRR releases enormous heat, which raises reaction temperatures to approach the melting temperatures of Ti, Zn, Mn, and Co. [ 14 ] Thus, the freshly formed Ti, Zn, Mn, and Co particles agglomerate, resulting in enlarged crystallite sizes. In contrast, Mo and W crystallites are small due to their inherently high melting points.…”
Section: Figurementioning
confidence: 99%
“…For example, two-dimensional graphene nanosheets, one-dimensional graphene nanoribbons, and zero-dimensional graphene quantum dots have been obtained9111213. Moreover, activated graphene14, graphene-assembled foam15, graphene paper16, graphene fiber17, graphene-based hydrogel or aerogel1819 and nanoporous graphene2021 materials have been synthesized by different methods, and the obtained materials were used to prepare macroscopic, large dimension monolith for further applications. As a result, the performance of graphene-based materials used as electrode in supercapacitors has been improved4514151617181920.…”
mentioning
confidence: 99%